Factors Affecting The Increase In Crime Index In West Sumatra With Path Analysis Method - Tarigan, Enita Dewi; Thoriq , Ahmad; Siringoringo, Yan Batara Putra; Hasibuan, Citra Dewi (Journal of Research in Mathematics Trends and Technology, 2022)
Crime or criminality in Indonesia is rampant in both print and television media. We can see news about crime almost every day. Basically, every individual will be influenced by several factors, both internal and internal, external causes of a person committing a crime, including population, education, morality, poverty and unemployment. In this case, a statistical analysis will be studied that can detect the magnitude of these factors, both directly and indirectly, on the crime rate. One of the statistical analyzes that can be used to analyze causal relationships between variables is path analysis, which is a direct development of the multiple regression form with the aim of providing estimates of the level of importance (magnitude) and significance (significance) in a variable set of causal relationships. hypothetical consequences. From the research results for West Sumatra Province, it was concluded that there was no large influence of variable X on Y